PERLINDUNGAN HUKUM PROFESI DOKTER DALAM PENYELESAIAN SENGKETA MEDIS - Setyo Trisnadi (Jurnal Pembaharuan Hukum, 2017)
This study aims to explore the analysis of the application of legal protection and its weaknesses in the settlement of medical disputes between physicians and patients today. Descriptively analytical and empirical juridical approaches, and using constructivism paradigm,it is hoped that the authors can describe various primary and secondary data to reconstruct the legal protection of the physician profession in the settlement of medical dispute between physicians and patients based on the value of justice. In the resolution of medical disputes between physicians and patients as set forth in Article 50 of Law No. 29 of 2004 on Medical Practice and Article 57 Law No. 36 Years of Health Personnel has not fully provided protection for doctors, because in practice the handling of alleged malpractice cases by the police investigator will certainly use the procedures or procedures in the KUHAP as a reference, this is because the Law does not regulate how to be in the event of suspicion that doctorsviolate articles In UUPK. The Government and House of Representatives are expected to make improvements to Law No. 29 of 2004 on Medical Practice, by making regulations on “procedural arrangements” ranging from inquiry, investigation, prosecution if necessary to verdict.